Climate change adaptation: a study of multiple climate-smart practices in the Nile Basin of Ethiopia - Teklewold, Hailemariam; Mekonnen, Alemu; Köhlin, Gunnar (Climate and development (Print), 2018)
Formulae display:?Mathematical formulae have been encoded as MathML and are displayed in this HTML version using MathJax in order to improve their display. Uncheck the box to turn MathJax off. This feature requires Javascript. Click on a formula to zoom.
Keywords: openalex:import

Agricultural Adaptation to Climate Change in Africa - Levin, Jörgen; Köhlin, Gunnar; Mekonnen, Alemu (2018)
This chapter asks whether there will be positive or negative impacts on smallholder farmers and rural households as more agricultural land is used for biofuels production. The study uses a computab ...
Keywords: openalex:import